2015
DOI: 10.1007/s10792-015-0158-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and surgical outcomes of pediatric rhegmatogenous retinal detachment

Abstract: The objective of this study was to analyze the characteristics and surgical results of pediatric rhegmatogenous retinal detachment (RRD). The medical records of 30 eyes of 29 patients younger than 18 years of age who underwent vitreoretinal surgery due to RRD were analyzed. The gender, age, laterality, duration of presenting symptom, etiology, ocular and systemic co-morbidities, type of breaks, lens status, presence of proliferative vitreoretinopathy (PVR) and its grade, initial and final best-corrected visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 18 publications
8
41
1
24
Order By: Relevance
“…In our subgroup of RD in children with congenital or developmental ocular abnormalities, the mean age was significantly lower (7.3 years, SD 5.9). Consistent with other reports, we found a strong male predominance (77%) [1,4,7,14,[16][17][18] . In the trauma group, the percentage of boys was even higher (87%).…”
Section: Demographic Data and Clinical Symptomssupporting
confidence: 92%
See 4 more Smart Citations
“…In our subgroup of RD in children with congenital or developmental ocular abnormalities, the mean age was significantly lower (7.3 years, SD 5.9). Consistent with other reports, we found a strong male predominance (77%) [1,4,7,14,[16][17][18] . In the trauma group, the percentage of boys was even higher (87%).…”
Section: Demographic Data and Clinical Symptomssupporting
confidence: 92%
“…RD in children commonly occurs in early puberty [4] . Similar to our data, other authors reported a mean age between 8.3 and 12.5 years [8,14,16,17] . In our subgroup of RD in children with congenital or developmental ocular abnormalities, the mean age was significantly lower (7.3 years, SD 5.9).…”
Section: Demographic Data and Clinical Symptomssupporting
confidence: 92%
See 3 more Smart Citations